Phase Manifestation and Formation of Nanoemulsions Composed of Imidazolium-based Ionic Liquid, Tween 80/Span 80 and Labrafac Lipophile WL 1349 - S. H. Ng; P. M. WOI; C. C. ENG (Universitas Gadjah Mada, 2015)
onic liquids (ILs) can enhance topical and transdermal delivery, as well as increase the solubility of sparingly soluble drugs. In the present work, pseudo-ternary phase diagrams of emulsions were composed of a mixture of non-ionic surfactants, polyoxyethylene sorbitan monooleate (Tween 80®) and sorbitan monooleate (Span 80®) in weight fraction: 1:1, 1:2, 2:1 and 2:3, LabrafacTM Lipophile WL 1349 as an oil phase and 1-hexyl-3-methylimidazolium chloride [(HMIM) (Cl)] as a continuous phase. Emulsion formulations were selected with 10% surfactants from the pseudo-ternary phase diagrams and further prepared at 298.2 ± 0.1 K. Acoustic emulsificationmethod was used to prepare nanoemulsions that were mixed with freshly prepared hydrocolloid gum. The area of the single-phase zone in pseudo-ternary phase diagrams that varied with Tween 80® /Span 80® ratio in the order of 2:1 > 1:1 > 2:3 > 1:2 where Span 80® was replaced by an equivalent weight of Tween 80® to form IL-based nanoemulsions. [HMIM] [Cl] tended to create a two-phase system. Addition of carbopol® ultrez 20 copolymer into the continuous phase of the formulations gave single-phase nanoemulsions with good stability. The mixture of surfactants with weight ratio of 1:2 (Tween 80®/Span 80®) showed a good stability with the smallest particle size and greater surface charges in the system. These ionic liquid-based nanoemulsions might have the potential in drug delivery systems.